The context, contribution and consequences of addressing the COVID‐19 pandemic: A qualitative exploration of executive nurses' perspectives. (15th February 2022) - Riddell, Kathryn; Bignell, Laura; Bourne, Debra; Boyd, Leanne; Crowe, Shane; Cucanic, Sinéad; Flynn, Maria; Gillan, Kate; Heinjus, Denise; Mathieson, Jac; Nankervis, Katrina; Reed, Fiona; et al.
Abstract: Aims: To explore (1) the context in which nursing executives were working, (2) nursing's contribution to the healthcare response and (3) the impact from delivering healthcare in response to the pandemic. Design: Retrospective, constructivist qualitative study. Methods: Individual interviews using a semi‐structured interview guide were conducted between 12 February and 29 March 2021. Participants were purposively sampled from the Victorian Metropolitan Executive Directors of Nursing and Midwifery Group, based in Melbourne, Victoria the epi‐centre of COVID‐19 in Australia during 2020. All members were invited; 14/16 executive‐level nurse leaders were participated. Individual interviews were recorded with participant consent, transcribed and analysed using thematic analysis. Results: Four inter‐related themes (with sub‐themes) were identified: (1) rapid, relentless action required (preparation insufficient, extensive information and communication flow, expanded working relationships, constant change, organizational barriers removed); (2) multi‐faceted contribution (leadership activities, flexible work approach, knowledge development and dissemination, new models of care, workforce numbers); (3) unintended consequences (negative experiences, mix of emotions, difficult conditions, negative outcomes for executives and workforce) and (4) silver linings (expanded ways of working, new opportunities, strengthened clinical practice, deepened working relationships). Conclusion: Responding to the COIVD‐19 health crisis required substantial effort, but historical and industrial limits on nursing practice were removed. With minimal information and constantly changing circumstances, nursing executives spearheaded change with leadership skills including a flexible approach, courageous decision‐making and taking calculated risks. Opportunities for innovative work practices were taken, with nursing leading policy development and delivery of care models in new and established healthcare settings, supporting patient and staff safety. Impact: Nursing comprises the majority of the healthcare workforce, placing executive nurse leaders in a key role for healthcare responses to the COVID‐19 pandemic. Nursing's contribution was multi‐faceted, and advantages gained for nursing practice must be maintained and leveraged. Recommendations for how nursing can contribute to current and future widespread health emergencies are provided.